The Th17-Defining Transcription Factor RORγt Promotes Glomerulonephritis - Steinmetz, Oliver M. (American Society of Nephrology, 2011)
Although Th17 responses may contribute to the pathogenesis of glomerulonephritis, whether the key transcription factor in Th17 cell development, RORγt, also promotes glomerulonephritis is unknown. Here, we induced crescentic glomerulonephritis in wild-type and RORγt-deficient (RORγt(−/−)) mice. RORγt(−/−) mice were protected from disease, with reduced histologic and functional injury and decreased leukocyte infiltration. Because RORγt(−/−) mice lack lymph nodes, which may influence the development of nephritis, we performed cell-transfer studies. We reconstituted Rag1(−/−) mice, which lack adaptive immunity but otherwise have normal architecture of the lymphatic system, with splenocytes from naïve wild-type or RORγt(−/−) mice. Mice receiving wild-type splenocytes exhibited high mortality from renal failure after induction of nephritis whereas mice receiving RORγt(−/−) cells were protected. To determine the effect of RORγt deficiency specifically in T helper cells, we isolated naïve CD4(+) T cells from wild-type and RORγt(−/−) mice and transferred them into Rag1(−/−) animals. Recipients of wild-type CD4(+) T cells developed severe glomerulonephritis whereas recipients of RORγt(−/−) cells developed less severe disease. To exclude effects of altered regulatory T cell (Treg) development caused by RORγt deficiency, we transferred naïve CD4(+) T cells depleted of Tregs into Rag1(−/−) mice. Recipients of wild-type, Treg-depleted, CD4(+) T cells developed severe glomerulonephritis whereas recipients of RORγt(−/−), Treg-depleted CD4(+) T cells did not. Taken together, this study demonstrates that RORγt promotes the development of crescentic glomerulonephritis by directing nephritogenic Th17 responses.